Cognitive Freedom: Human Rights Born from Today's Artificial Intelligence - Favio Farinella; Elena Gulyaeva (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
When the manipulation of the human brain activity is a real possibility as happens nowadays, a minimum of ethical values should be respected and incorporated into international and domestic Law. These rules shall aim to regulate the application of neurotechnologies and artificial intelligence to the human brain. No State which claims to be respectful of human rights can exercise the power to coercively manipulate the mental states of its population. In this article, we discuss cognitive freedom, a new right born out of neurotechnologies, which can also be understood as an update of human free will adapted to the 21st century. It is -as we will see- a multidimensional concept, difficult to define due to its complexity. In this article, we propose to consider cognitive freedom as an entirely new human right aimed at preserving the very essence of human nature. To validate our hypothesis, we use a qualitative methodology, aimed at establishing a consensual opinion of experts in the legal and scientific fields, together with the assistance of the main sources of the law, namely positive law, case law and doctrine.